Whiskey & tangerines: An ethnodrama exploring a couple’s transition from alcoholism to long-term recovery - Maxfield, Paul (Kansas State University, 2018)
According to SAMHSA statistics, about 22 million people in the US meet the criteria for a Substance Use Disorder (SUD), with alcohol use disorders (AUDs) being the most prevalent form of SUD. Of those with SUDs, only 10% or two million receive formal treatment. It is estimated that 64% of those completing treatment for SUDs relapse within the first year of sobriety. However, for individuals who manage to make it five years without relapsing, the risk of relapse reduces to 14%, suggesting that the needs of individuals in short-term recovery differ from those in long-term recovery. It has also been found that family involvement in the treatment and recovery process is beneficial to individuals in recovery. However, SUDs contribute to elevated levels of stress and dissatisfaction in couples and families, which puts them at high risk for divorce or dissolution prior to individuals seeking treatment. For families who remain intact until the individual completes treatment, the transition to a recovery lifestyle that supports the individual’s recovery presents a different set of challenges. Additionally, lingering frustrations and resentments from the period of active addiction may also serve to destabilize the couple or family, contributing to the high levels of divorce among those recovering from SUDs. In short, few couples are able to sustain their partnerships through active addiction, and the transition to recovery. While these couples are in the minority, their successful experiences can provide valuable insight into the recovery process. The present study examines the successful transition from active addiction to long-term recovery for one such couple. In particular, the study investigates the shifting narratives related to family roles, couple-hood, communication, alcohol, alcoholism, and recovery. The data is presented in the form of an ethnodramatic script. Ethnodrama is used to engage audiences both on emotional as well as informational levels. While ethnodrama may not provide specific answers, it is intended to provoke awareness, insight, and discussion by allowing audiences to vicariously experience the represented lives of the participants. Following the ethnodrama, an analysis of the script is presented, incorporating narrative theoretical frameworks so that the ways in which narratives function to facilitate (or frustrate) change within the individuals as well as the dynamics of the couple relationship can be expanded. The result of this analysis is the production of a Narrative Change Model, which can be useful in understanding the ways that narratives operate within the transition from active addiction to long-term sobriety and may have broader implications in explaining the narrative mechanisms behind other, more subtle change processes.
Keywords: Counseling; Alcoholism; Recovery; Narrative therapy; Couples; Ethnodrama